Mechanical behaviors of carbon fiber composite sandwich columns with three dimensional honeycomb cores under in-plane compression - Xiong, Jian (2013)
Mechanical properties and failure modes of carbon fiber composite egg and pyramidal honeycombs cores under in plane compression were studied in the present paper. An interlocking method was developed for both kinds of three-dimensional honeycombs. Euler or core shear macro-buckling, face wrinkling, face inter-cell buckling, core member crushing and face sheet crushing were considered and theoretical relationships for predicting the failure load associated with each mode were presented. Failure mechanism maps were constructed to predict the failure of these composite sandwich panels subjected to in-plane compression. The response of the sandwich panels under axial compression was measured up to failure. The measured peak loads obtained in the experiments showed a good agreement with the analytical predictions. The finite element method was used to investigate the Euler buckling of sandwich beams made with two different honeycomb cores and the comparisons between two kinds of honeycomb cores were conducted.